Development of Starch-Based Bioplastic from Jackfruit Seed - Trieu Khoa Nguyen; Nguyen Thy Ton That; Nien Thi Nguyen; Ha Thi Nguyen (Advances in Polymer Technology)
In this article, jackfruit seed starch plasticized with common plasticizers was developed and characterized. At the first step, the research papers that dealt with the fabrication and characterization of starch-based bioplastics were synthesized and analyzed. Next, jackfruit seeds were selected as a source for starch because of their large availability, low price or even free, and high starch capacity. Afterward, a starch-based bioplastic fabrication procedure was proposed. From preliminary tests, plasticizers were sufficiently selected, including water, glycerol, natri bicarbonate, and acid citric. Using different combinations of these plasticizers, four types of bioplastics were then fabricated to study the effect of the plasticizers as well as to characterize the properties of the corresponding bioplastics. A cutting tool for ASTM D412 type A standard tensile testing specimen was then designed and fabricated. Using these dog-bone specimens, tensile results showed that the hardness of the fabricated bioplastic was positively proportional to the ratio of the starch. Furthermore, from SEM characterization, the bioplastic specimens were fully plasticized. Although the fabricated bioplastic has lower mechanical properties than petroleum-based plastics, its environmental friendliness and high potential added value promise to be a material of the future.